2003
DOI: 10.1086/345828
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysics of Young Star Binaries

Abstract: This paper describes our study of the astrophysics of individual components in close pre-main-sequence binaries. We observed both stars in 17 systems, located in 4 nearby star forming regions, using low-resolution (R=760), infrared spectroscopy and photometry. For 29 components we detected photospheric absorption lines and were able to determine spectral type, extinction, K-band excess, and luminosity. The other 5 objects displayed featureless or pure emission line spectra. In ~50 % of the systems, the extinct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
203
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(227 citation statements)
references
References 75 publications
22
203
1
1
Order By: Relevance
“…The SED that results from our best model for AS 205 N differs by about 40% from the photometric measurements of Prato et al (2003) in the NIR wavelength range (Fig. 2).…”
Section: As 205 Nmentioning
confidence: 56%
See 1 more Smart Citation
“…The SED that results from our best model for AS 205 N differs by about 40% from the photometric measurements of Prato et al (2003) in the NIR wavelength range (Fig. 2).…”
Section: As 205 Nmentioning
confidence: 56%
“…There are previous flux measurements in the NIR and MIR wavelength ranges that can be exclusively ascribed to the northern component (Eisner et al 2005;Prato et al 2003). Apart from a recent observation at a wavelength of 860 μm (Andrews et al (2011), we assumed that all other previous photometric measurements could not spatially resolve each single component of the system.…”
Section: As 205 Nmentioning
confidence: 99%
“…It is a young (∼ 0.5 Myrs) late-type dwarf (≈K5) with mean V=12.4 mag that belongs to a hierarchical triple system. At an angular separation of 1.3 ′′ (≈180 AU at 140 pc) from AS 205A lies a very low-mass (K7/M0) spectroscopic binary (Ghez et al 1993;Prato et al 2003;Eisner et al 2005). An extensive photometric survey by Artemenko et al (2010) revealed two distinct and stable periods (P 1 =6.78 and P 2 =24.78 days) in the power spectrum of the light variations of AS 205A.…”
Section: Introductionmentioning
confidence: 99%
“…′′ 95-17. ′′ 0 in the star-forming regions of Taurus (distance 140 pc; Torres et al 2007, age 1-2 Myr; Kraus & Hillenbrand 2009a) and Ophiuchus (distance 140 pc; Loinard et al 2008, age 1 Myr; Allers et al 2006;Luhman & Rieke 1999;Prato et al 2003) were extracted from the literature (Kraus et al 2011;Kraus & Hillenbrand 2009b;Duchêne et al 2007;Ratzka et al 2005;Haisch et al 2004;Haisch et al 2002;White & Ghez 2001;Köhler & Leinert 1998;Reipurth & Zinnecker 1993;Leinert et al 1993) (see also Table 1 for references on each object).…”
Section: Sample and Archival Datamentioning
confidence: 99%
“…Since contamination of these sources can affect the discussion of disk frequency at the age of 1-2 Myr, we eliminated these sources from our sample. For Ophiuchus, VSSG 23 was removed from our sample due to their non-coevality (d∆ log(t) ∼ 1; Prato et al 2003). Unfortunately, sufficient data on coevality and proper motions were not available for many of the Ophiuchus sources, and these systems remain to be included in the sample as binary candidates.…”
Section: Sample and Archival Datamentioning
confidence: 99%